2011
DOI: 10.1155/2011/145640
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Silkworm Lines against Variations in Temperature and RH for Various Parameters of Commercial Cocoon Production

Abstract: Eleven inbred silkworm lines (M-101, M-103, M-104, M-107, Pak-1, Pak-3, Pak-2, Pak-4, PFI-1, PFI-2, and S-1) were evaluated for various parameters of cocoon production under different temperature and relative humidity conditions (25±1, 30±1, and 35±1• C in combination with 55, 65, and 75% RH for three hrs during 4th and 5th instar. The experiment was laid out in factorial design with three replications. Significant variations in the performance of silkworm lines were noticed due to influence of temperature and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
4
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 8 publications
(9 reference statements)
2
4
0
1
Order By: Relevance
“…These results ensure the performance hybrids will be changed in different environments (locations). These results are compatible with the findings of Hussain et al (2011) who reported that the average of evaluation index values for different traits showed that Pak-4 (61.42) was the best line followed by M-101 (59.15), Pak-2 (56.37), Pak-3 (52.83) PFI-I (52.62), and M-107 (50.03). The study clearly underlines the importance of optimization of environmental conditions during larval rearing in relation to commercial cocoon production.…”
Section: Data Insupporting
confidence: 92%
See 1 more Smart Citation
“…These results ensure the performance hybrids will be changed in different environments (locations). These results are compatible with the findings of Hussain et al (2011) who reported that the average of evaluation index values for different traits showed that Pak-4 (61.42) was the best line followed by M-101 (59.15), Pak-2 (56.37), Pak-3 (52.83) PFI-I (52.62), and M-107 (50.03). The study clearly underlines the importance of optimization of environmental conditions during larval rearing in relation to commercial cocoon production.…”
Section: Data Insupporting
confidence: 92%
“…The average of CW, CSW, PW, CSR and SP traits is better for both sexes in Qalubyia governorate. Similar results are obtained by Hussain et al (2011) who evaluated eleven inbred silkworm lines for various parameters of cocoon production under different temperature and relative humidity conditions (25±1, 30±1 and 35±1•C in combination with 55, 65, and 75% RH) for three hrs during 4 th and 5 th instar. Significant variations in the performance of silkworm lines were noticed due to the influence of temperature and RH treatment on 4 th and 5 th instar larvae.…”
Section: Table 2 Regional Effect Of Different Locations For Fourteesupporting
confidence: 82%
“…The quality of the cocoons is determined by the hereditary nature of the silkworm strains and environmental conditions during rearing, spinning stage, etc. [ 112 ]. The requirements of a perfect cocoon are healthy (no defects), clean (clean white), the inside (pupa) not damaged or crushed, and a hard silk shell (layer of silk fibers) resistant to finger pressure.…”
Section: Examining Sericulture Development In Indonesiamentioning
confidence: 99%
“…Multidirectional Activities for Gene Pool Conservation in GCEARS-PSP were seriously investigated by Hussain et al (2011) in Pakistan and Chanda et al (2013) in India, countries with a long history in sericulture.…”
Section: Biological Indices Of Crude Cocoonsmentioning
confidence: 99%